Correlational Study Between Conceptual Understanding and Critical Thinking Skills of Students on Biology Materials - Bambang Rismanto; Muhammad Aqillul Hayat (Universal Education Jurnal Teaching and Learning, 2025)
This study aims to identify the relationship between students' understanding of biological concepts and their critical thinking skills. This research uses a quantitative approach with a correlational study design. The research was carried out in Tanjung Jabung Barat Regency, which involved a sample of 328 class XI students, who were selected using simple random sampling from a population of four selected high schools. The data was collected using two validated research instruments, namely the biology concept understanding test and the critical thinking skills test. Descriptive statistics and Pearson Product-Moment correlation were used to test the strength and direction of correlation between the two quantities. The average score for students' understanding of biology concepts was 59.32 (SD = 15.28), while the average score for critical thinking skills was 53.15 (SD = 9.20). This indicates that, on average, students still face difficulties in both aspects. The analysis results showed a significant positive correlation between students' understanding of biological concepts and their critical thinking skills (r = 0.797, p < 0.01). These findings indicate that a good understanding of biological concepts can improve students' critical thinking skills, which are essential for the development of higher-order thinking skills. The critical thinking scores are significantly explained by the students' conceptual understanding since R² = 0.635, which shows that the biological concepts comprehension could account for 63.5% of the critical thinking variance, while the other 36.5% will be due to other factors. These findings highlight the importance of understanding concepts for developing critical thinking skills. The study suggests that teaching strategies focusing on understanding the biological concepts that the students are being taught should come first for students to develop their higher-order thinking skills. Moreover, it is advisable to broaden the scope of contributing factors to encompass such issues as teaching approaches and students’ active participation in future studies. The findings offer useful information for the development of curricula, the goal of which is to integrate the conceptual understanding and critical thinking skills of those being taught biology.